Evaluation of Online teaching by Undergraduate medical students of Rawalpindi Medical University amidst COVID-19 pandemic - Rizwana Shahid, Shazia Zeb, Sumaira Yasmeen, Muhammad Umar, Rai Asghar, Maryim Batul (Journal of Rawalpindi Medical College, 2021)
Objective: To determine the viewpoints of undergraduate medical students pertinent to online education carried out by their teachers amid COVID-19 pandemic Subjects & Methods: A cross-sectional descriptive study was carried out during August 2020 in order to evaluate the teachers with respect to their online teaching. Google forms were electronically administered to all 1st – final year medical students to gather their perspectives relevant to their respective teachers. About 266 medical students participated in this research through convenience sampling. Mean ± SD for each item was computed. The data was analyzed by means of SPSS version 25.0. Results: Of the total 266 medical students, highest proportion (53.75%) was constituted by final year MBBS students. Maximum response was received pertinent to teachers of Pathology followed by those of Surgery & Allied, Medicine & Allied and Gynaecology & Obstetrics. Students were 100% satisfied with online teaching attributes of Surgery & Allied Teachers while % and % were pleased with those of Medicine & Allied and Gynaecology & Obstetrics respectively. Well preparedness of the teachers for their online class got highest score (4.49 ± 1.05) while least score (4.07 ± 1.44) was computed regarding flexibility of the teachers in accommodating individual student needs. Students recommended making the e-learning sessions more interactive. Conclusion: Medical students were sufficiently contented with online teaching of their respective teachers. However, there is need to train the teachers for more interactivity during e-learning sessions.